2011
DOI: 10.3133/pp1737b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeologic settings and groundwater-flow simulations for regional investigations of the transport of anthropogenic and natural contaminants to public-supply wells—Investigations begun in 2004

Abstract: Hydrogeologic settings and groundwater-flow simulations for regional investigations of the transport of anthropogenic and natural contaminants to public-supply wells-Investigations begun in 2004: U.S. Geological Survey Professional Paper 1737-B, 127 p. iii Foreword The U.S. Geological Survey (USGS) is committed to providing the Nation with reliable scientific information that helps to enhance and protect the overall quality of life and that facilitates effective management of water, biological, energy, and min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Sites with dominantly lognormal IRFs are located where the Edwards aquifer is wide (Fig. 2); in this area Eberts (2011) reported that groundwater flows southwesterly, then sweeps around to the northeast, with a strong regional flow component. Sites with dominantly exponential IRFs are located where the Edwards aquifer is narrow, and flow in this area is to the north-northeast along a series of conduit-controlled flow paths (Hunt et al, 2006).…”
Section: Edwards Aquifermentioning
confidence: 99%
“…Sites with dominantly lognormal IRFs are located where the Edwards aquifer is wide (Fig. 2); in this area Eberts (2011) reported that groundwater flows southwesterly, then sweeps around to the northeast, with a strong regional flow component. Sites with dominantly exponential IRFs are located where the Edwards aquifer is narrow, and flow in this area is to the north-northeast along a series of conduit-controlled flow paths (Hunt et al, 2006).…”
Section: Edwards Aquifermentioning
confidence: 99%